Application of Capital Punishment for Narcotics Offenders in the Perspective of Responsive Law: Penerapan Sanksi Pidana Mati terhadap Pelaku Kejahatan Narkotika dalam Perspektif Hukum Responsif. - Pahlevi, Muhammad Alief Yunas; Haruni, Catur Wido; Prasetyo, Said Noor (Rechtsidee, 2023)
This study employs a normative legal research method, grounded in the Nonet and Selznick theory of responsive law, to examine the implementation of capital punishment for narcotics offenders in Indonesia. Evaluating the punitive measures through the lens of responsiveness to societal goals, participation of vulnerable groups, and legal institutions' balanced response, the research highlights the need for a nuanced approach. Findings indicate that the current use of capital punishment lacks effectiveness and contradicts human rights principles. The study suggests a reassessment, prioritizing rehabilitation and decriminalization for a more humane and sustainable approach to combating narcotics trafficking. Highlights: The study reevaluates the application of capital punishment for narcotics crimes in Indonesia through the lens of responsive legal principles. Findings underscore the ineffectiveness of the current punitive measures and their conflict with human rights norms. The research advocates for a reconsideration of the approach, emphasizing rehabilitation and decriminalization to achieve a more humane and sustainable strategy against narcotics trafficking. Keywords: Capital Punishment, Narcotics Offenses, Responsive Law, Human Rights, Rehabilitation.